Atrophy of the lower limbs in elderly women: is it related to walking ability? - Ikezoe, Tome; Mori, Natsuko; Nakamura, Masatoshi; Ichihashi, Noriaki (European journal of applied physiology, 2011)
This study investigated the relationship between walking ability and age-related muscle atrophy of the lower limbs in elderly women. The subjects comprised 20 young women and 37 elderly women who resided in nursing homes or chronic care institutions. The elderly subjects were divided into three groups according to their walking ability. The muscle thickness of the following ten lower limb muscles were measured by B-mode ultrasound: the gluteus maximus, gluteus medius, gluteus minimus, psoas major, rectus femoris, vastus lateralis, vastus intermedius, biceps femoris, gastrocnemius and soleus. Compared to the young group, muscle thicknesses of all muscles except the soleus muscle were significantly smaller in all the elderly groups. There were no significant differences between the fast- and slow-walking groups in the thickness of any muscle. In the dependent elderly group, noticeable muscle atrophy was observed in the quadriceps femoris muscle. The results of this study suggest that the elderly who are capable of locomotion, regardless of their walking speed, show a moderate degree of age-related atrophy, while those who do not walk exhibit more severe atrophy, especially in the quadriceps femoris muscle.